1977
DOI: 10.1161/01.cir.55.3.479
|View full text |Cite
|
Sign up to set email alerts
|

Pre and postoperative ventricular function in infants and children with right ventricular volume overload.

Abstract: Hemodynamic and ventricular volume parameters were evaluated in 21 patients (24 studies) with total anomalous pulmonary venous return (TAPVR), 11 patients with secundum atrial septal defect (ASD), and eight patients who had complete correction of TAPVR or ASD. Right and left ventricular (RV and LV) volume parameters were calculated according to Simpson's rule and the area length methods, respectively. In infants with TAPVR, RV end-diastolic volume was larger than normal, but RV ejection fraction was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Some studies have demonstrated that after closure of the defect, end-diastolic diameters and volumes of LV and RV change towards normal values [33, 34]. Similarly, in our patients, size of LV increased during follow-up, and no difference was present between patients and controls 6 months after treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Some studies have demonstrated that after closure of the defect, end-diastolic diameters and volumes of LV and RV change towards normal values [33, 34]. Similarly, in our patients, size of LV increased during follow-up, and no difference was present between patients and controls 6 months after treatment.…”
Section: Discussionsupporting
confidence: 74%
“…In both of our studies, preoperative mean PA pressure values were significantly higher, whereas on the contrary, left ventricular area and volume values were lower in Group 1. This can be explained with the fact that majority of the patients in Group 1 had obstructive type anomalies (p<0.05), because presence of pulmonary venous hypertension causes increased right ventricle afterload, shifting of the septum towards left ventricle and finally underdeveloped left ventricular cavity (14,15). Mean age of patients at the time operation was also lower in Group 1, which may be another factor causing difference in sizes of the cardiac chambers between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…[17] and Nakazawa et al . [20] suggests : (a) preoperatively, the left ventricular size, ejection fraction, and systolic output are often decreased ; (b) these decreases probably result from a decreased volume load to the left ventricle ; (c) pulmonary symptoms result from venous obstruction and not from ventricular dysfunction ; and (d) decreased left ventricular size and function do not affect operative mortality and are reversed with early repair. These conclusions are supported by our current series .…”
Section: Discussionmentioning
confidence: 99%